Expansão e democratização da educação superior: uma avaliação dos impactos do REUNI no curso de Serviço Social da UFPB - Costa Filho , Evandro Soares (2016)
The current expansion process of higher education in Brazil occurs in accordance with contemporary changes identified in the production and valuation of capital articulated to the transnational political agenda which follows the productive restructuring and neoliberal policies. However, such expansion process gains strength with the Brazilian State Reform implemented in the 1990s, whose main goals were to redefine the government’s responsibilities in relation to social services, privatizations, and reducing public spending. The consequences of this Reform have had a major impact on the offering of social security services and also in the education field. Public universities have suffered not only with budget cuts, compromising their autonomy, but also with changes in their courses’ curricula to attend market demands. As an attempt to implement a new university model, former Brazilian president Lula creates, in 2007, the Program of Support for the Restructuring and Expansion of Federal Universities (REUNI, in Portuguese), as one of the policies to restructure public higher education in Brazil by providing more opportunities of access and permanence of students from less favored social classes, and as such, highlights the commitment with the democratization of public higher education. Taking these ideas into account, the aim of this work is to investigate the current process of expansion and democratization of higher education in Brazil, emphasizing the impacts of REUNI at Federal University of Paraiba (UFPB, in Portuguese), more specifically, in the undergraduate course of Social Service, by observing the gradual increasing number of enrolled students after REUNI. Our study can be defined as an ex-post facto focusing on the quanti-qualitative dimension, making use of historical and dialectical methods, taking into consideration the reality/possibility category for the object analysis. Regarding the technical procedures, we have decided to use bibliographic and documentary research by selecting sources and documents related to higher education area, the implementation of REUNI at UFPB, reports of the Information Technology Oversight Committee at UFPB, and also meeting records of Social Service teachers’ department, and of Human Sciences, Language and Arts Centre council which discussed the restructuring program. The data collection occurred between the months of June and July 2016. The current onrush in higher education intensifies, in a exponential way, its inclination to attend marked needs, based on a neoconservative wave in Brazilian higher education, incorporating the concept of enterprise rationality, uncompromised with the right to under-privileged people from our society have access to quality public education.